An exploratory research on the centre for academic information services, UNIMAS, that whether this department meets the needs of the direct and indirect customers / Sulian Mohammad Alias - Mohammad Alias, Sulian (2001)
This study was undertaken to determine the consumers’ awareness of the Centre for Academic Information Services (CAIS) library services in Universiti Malaysia Sarawak (UNIMAS) available to them and to find out whether they are satisfied with CAIS services or vice versa. Furthermore it aims to find out the strengths and weaknesses ofthe existing library services, facilities and resources. Besides that, the study hoped to provide improvement to the existing library services in terms oflibrary operations, equipment and technology with a view to further enhance the service quality. This study also hoped to assess the adequacy, relevance and updated collection of materials and references that can provide and support students’ study, research work and academic programs.